PENGARUH BUDAYA KERJA DAN PROFESIONAL GURU TERHADAP PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR BAHANA ISLAMIC SCHOOL KOTA MAKASSAR - Namirah, Alya; Siradjuddin; Kasmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
When the work culture and teacher profession are not optimal, the impact is very felt on the learning motivation of students. Failure to improve learning motivation not only harms individual students, but also has an impact on overall academic achievement and creates a less productive school environment.The research approach used in this study is correlation approach. In the context of this study, the focus is to identify the relationship between work culture and teacher profession and the increase in students' learning motivation in elementary school. The data collection method uses interviews, observations, and questionnaires.This study has shown several key findings related to the influence of work culture and teacher professionalism on the learning motivation of students at Bahana Islamic School Elementary School. First, the results of the analysis show that there is a positive and significant relationship between work culture in schools and students' learning motivation. Second, that the influence of teacher professionalism is not statistically significant so that the influence of teacher professionalism on student learning motivation cannot be considered significant. Third, overall, the study shows that both work culture and teacher professionalism together have a positive relationship with learn-ing motivation. However, only work culture has been proven to be significant in influencing students' motivation to learn individually, while professionalism has not shown a significant influence. These results explain the importance of developing a conducive work culture to increase participants' learning motivation